Energy Profile of Faster-than-Light Particles : A New Approach to The Special Theory of Relativity - Matradji Matradji; Tutug Dhanardono; Heri Justiono (Institut Teknologi Sepuluh Nopember, 2015)
It is known that neutrinos propagate faster than light. For that reason the Einstein’s special theory of relativity cannot be applied to these phenomena. On the other hand the Matscie’s special theory of relativity based on the Matscie’s transformation is valid for any velocity including the velocities greater than the velocity of light in free space. The relativistic phenomena consisting of the length contraction and the time dilation can be verified successfully by the Matscie’s special theory of relativity. In this case, the velocity of light in free space acts as the critical velocity. Only about 81.6% of the rest mass of a body can be converted into energy. At very low velocities, the kinetic energy of a moving body is practically the same as that in the classical mechanics. And also at velocities of much higher than the critical velocity, it almost reduces to the classical expression. For moderate velocities, the Matscie’s special theory of relativity reduces to the Einstein’s special theory of relativity. For velocities close to (below or above) the velocity of light in free space, the kinetic energy of a moving body differs from that predicted by the classical mechanics.